Survey of postoperative residual curarization, acute respiratory events and approach of anesthesiologists - Aytac,Ismail (2016)
BACKGROUND AND OBJECTIVES: residual paralysis following the use of neuromuscular blocking drugs (NMBDs) without neuromuscular monitoring remains a clinical problem, even when NMBDs are used. This study surveys postoperative residual curarization and critical respiratory events in the recovery room, as well as the clinical approach to PORC of anesthesiologists in our institution. METHODS: This observational study included 415 patients who received general anesthesia with intermediate-acting NMBDs. Anesthesia was maintained by non-participating anesthesiologists who were blinded to the study. Neuromuscular monitoring was performed upon arrival in the recovery room. A CRE was defined as requiring airway support, peripheral oxygen saturation <90% and 90-93% despite receiving 3 L/min nasal O2, respiratory rate >20 breaths/min, accessory muscle usage, difficulty with swallowing or speaking, and requiring reintubation. The clinical approach of our anesthesiologists toward reversal agents was examined using an 8-question mini-survey shortly after the study. RESULTS: The incidence of PORC was 43% (n = 179) for TOFR <0.9, and 15% (n = 61) for TOFR <0.7. The incidence of TOFR <0.9 was significantly higher in women, in those with ASA physical status 3, and with anesthesia of short duration (p < 0.05). In addition, 66% (n = 272) of the 415 patients arriving at the recovery room had received neostigmine. A TOFR <0.9 was found in 46% (n = 126) of the patients receiving neostigmine. CONCLUSIONS: When routine objective neuromuscular monitoring is not available, PORC remains a clinical problem despite the use of NMBDs. The timing and optimal antagonism of the neuromuscular blockade, and routine objective neuromuscular monitoring is recommended to enhance patient safety.